POWDER PROCESSING AND BINDER REMOVAL STUDIES FOR THE FABRICATION OF DEFECT FREE BORON CARBIDE PELLETS - Qureshi, A. H.; Shahzad, K.; Hussain, N.; Nawaz, M. R.; Musaddiq, M.; Ahmed, N.; Qazi, N. K. (The Nucleus, 2020)
Compaction behaviour of boron carbide (B4C) has been studied by pressing the powder at different load with and without the lubrication of powder and die walls. The study was mainly focused on the optimization of powder processing, compaction, binder removal and sintering conditions. The results clearly suggest that the binder removal rate during the sintering caused the formation of cracks and pores. However, these defects have been eliminated by removing the binder before sintering. The endcapping problem of pellets was controlled by lubricating the powder and die walls. B4C pellets with required dimensions were produced using uniaxial die-compaction and pressureless sintering technique.